Nitrogen and Sulfur Fertilization Effects on Camelina Sativa in West Central Kansas - E. Obeng; A. Obour; N. O. Nelson (Kansas Agricultural Experiment Station Research Reports, 2016)
Camelina sativais early maturing and possesses characteristics that make it a good fit as a rotation crop in dryland wheat cropping systems. Nitrogen (N) and sulfur (S) play very important roles in oilseed production, including camelina. This study was conducted over 3 years to determine N and S rates necessary for optimum camelina production in west central Kansas. The experiment was set up as randomized complete blocks with four replications in a split-plot arrangement. Treatments were two sulfur rates (0 and 18 lb/a) as the main plots, and four N rates (0, 20, 40, and 80 lb/a) as the sub-plot. Sulfur application did not affect stand count, biomass yield, harvest index, seed yield, oil and protein content. However, stand count, biomass yield, seed yield, and protein content were affected by N application (P<0.05). Average oil and protein content were 28.1% and 33.9% respectively. The optimum N rate for yield was 20 lb N/a, which produced around 680 lb/a seed yield. Based on soil test levels of 25 lb N/a, N requirement for camelina production is 45 lb N/a.
Keywords: Camelina; nitrogen; and sulfur